Inhibition of HO-1 enzymatic activity impairs head and neck cancer cell survival - Mascaró, Marilina (2021)
We have previously reported that, in human HNSCC samples, hemeoxygenase-1 (HO-1) mRNA expression is up-regulated and it is associated with worst survival. We also reported an up-regulation of HO-1 protein levels and that it is localized in the cytoplasmic and nuclear compartments. Moreover, we demonstrated that pharma- cological activation of HO-1 by hemin and genetic full-length HO-1 (FL-HO-1) overexpression increases HN13 cells survival and cell cycle progression, suggesting a protumor role of HO-1 in HNSCC. However, whether byproducts of HO-1 enzymatic activity are in- volved in FL-HO-1 mediated-effects remains unknown. In this study, we aimed to elucidate if inhibition of HO-1 enzymatic activity impacts on head and neck cancer cells behavior. To that end, HO-1 activity was inhibited pharmacologically using ZnPP and an enzymatically inactive FL-H25A-HO1-overexpressing HN13 cell line was estab- lished. We evaluated HO-1 expression by western blot and indirect immunofluorescence, cell viability by crystal violet, cell proliferation by manual cell counting, cell cycle progression by propidium iodide staining and flow cytometry, and cell migration by wound healing assay. We found that 10 μM ZnPP impaired cell viability (p<0,001 vs DMSO) at 48h and 72h as well as it diminished cell number at 72h (p<0,01 vs DMSO). Also, in such conditions, ZnPP induces overex- pression of HO-1, which is localized in the cytoplasm. In line with the previously mentioned, we found that FL-H25A-HO1 HN13 cells have a lower growth rate (p<0,001) than FL-HO1 HN13 cells. We also found that the population of FL-H25A-HO1 HN13 cells have an increase in Go/G1 phase (p<0,01) and a decrease in G2/M phase (p<0,05) compared with FL-HO1 HN13 cells. Related to cell migra- tion, FL-H25A-HO1 failed to alter migratory capacity (p>0,05 vs FL- HO1). In conclusion, our results show that the enzymatic activity of HO-1 plays a role in the FL-HO-1-mediated effects on head and neck cancer cell survival.